Flypaper Effect dan Kapasitas Fiskal Daerah: Studi Empiris pada Kabupaten/Kota di Sulawesi Selatan - Ramadhani, Magfirah Wahyu; Utami, Sri; Majiding, Nurul Chalisa; Akib, Ambarwati (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
This study analyzes the influence of the Flypaper Effect on regional expenditure in regencies/cities in South Sulawesi Province, with fiscal capacity as a moderating variable. The Flypaper Effect occurs when regional expenditure is more influenced by transfers from the central government than by Local Revenue (PAD). This research uses secondary data from the Regional Budget (APBD) reports for the years 2021 to 2023 from 24 regencies/cities in South Sulawesi. Using multiple linear regression analysis, the results indicate that central government transfers, particularly the General Allocation Fund (DAU), have a significant impact on regional expenditure, while PAD contributes to a lesser extent. Furthermore, the moderating test results show that fiscal capacity, measured through PAD, does not significantly moderate the relationship between transfer funds and regional expenditure. These findings provide empirical evidence that despite regional fiscal capacity, reliance on central government transfers remains dominant in influencing regional expenditure. This study offers insights for local governments to focus more on increasing PAD to reduce dependence on central transfers and contributes to the development of fiscal decentralization theory